Penggunaan Narasi Abraham Dan Rahab Dalam Yakobus 2:21-26 - Joko Priyono; Yohanis Kamba (Predica Verbum: Jurnal Teologi dan Misi, 2022)
The use of Old Testament citation in the New Testament is the usage commonly used by New Testament writers. Likewise, the use of Abraham and Rahab's narrative in the context of faith and works in James 2:14-26, needs to be understood correctly. So that the text does not cause misunderstandings in interpreting the meaning of the theology of faith and deeds described by James. The author in this case uses the exegesis method of using the Old Testament in the New Testament presented by Grant R. Osborne to find the significance of the use of Abraham and Rahab's narrative in the topic of faith and works (Jas. 2:14-26). The narratives of Abraham and Rahab are authoritative illustrations or examples to respond to the thesis that faith and works are two separate things. James shows that faith and works are inseparable in the life of a true Christian.